Orchestrating immunopathology: the spectrum of programmed cell death pathways co-opted by influenza a virus in pulmonary immunity - Luo, Yuanyuan; Xiang, Li; He, Qingman; Gao, Yongxiang; Zheng, Chuan; Yao, Huan (Frontiers in Immunology, 2026)
Influenza A virus (IAV) infection activates multiple programmed cell death (PCD) pathways, which, while restricting viral replication and dissemination, concurrently disrupt the respiratory epithelial barrier and compromise immune homeostasis. Excessive activation of apoptosis, necroptosis, pyroptosis, and related processes results in tight junction(TJ) disruption, impaired mucociliary clearance and gas exchange, and amplification of inflammatory cascades, ultimately driving cytokine storm and severe tissue injury. This dual role of PCD underscores its importance in antiviral defense while exposing its potential to exacerbate immunopathology. Accordingly, this review focuses on IAV-induced PCD mechanisms, delineating their contribution to epithelial barrier breakdown and immune dysregulation, with the aim of informing strategies for precise modulation of immunopathological damage and improving therapeutic outcomes in severe influenza.